2016
DOI: 10.1016/j.biortech.2016.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Biosolids reduction by the oxic-settling-anoxic process: Impact of sludge interchange rate

Abstract: . D. (2016). Biosolids reduction by the oxicsettling-anoxic process: impact of sludge interchange rate. Bioresource Technology, Biosolids reduction by the oxic-settling-anoxic process: impact of sludge interchange rate AbstractThe impact of sludge interchange rate (SIR) on sludge reduction by oxic-settling-anoxic (OSA) process was investigated. The sludge yield of an OSA system (a sequencing batch reactor, SBR, integrated with external anoxic reactors) was compared to that of a control (an SBR attached to a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…This reduction has also been observed by other authors . Moreover, as can be seen from the reported values, the nitrate concentration in the effluent from Plant B was always lower than in Plant A, as the inclusion of an anoxic step in the biological process led to partial consumption of nitrate as an electron acceptor for the degradation of the substrate . The difference in nitrate concentration between the plants during the OSA phases was especially noticeable for Phase II.…”
Section: Resultssupporting
confidence: 85%
“…This reduction has also been observed by other authors . Moreover, as can be seen from the reported values, the nitrate concentration in the effluent from Plant B was always lower than in Plant A, as the inclusion of an anoxic step in the biological process led to partial consumption of nitrate as an electron acceptor for the degradation of the substrate . The difference in nitrate concentration between the plants during the OSA phases was especially noticeable for Phase II.…”
Section: Resultssupporting
confidence: 85%
“…Sewage sludge is an undesired by-product of wastewater treatment, which needs to be treated, and otherwise, may have a significant environmental impact (Li et al 2015;Guo et al 2013;Semblante et al 2016). In Europe, the annual production of sewage sludge accounted for more than 10 million tons in 2010 and is expected to increase to 13 million tons in 2020 (Paul and Debellefontaine, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of denitrification largely depends on the capacity of the preceding nitrification to produce nitrate, and therefore the efficiencies of the two reactions were related. In a previous OSA study, http://dx.doi.org/10.1016/j.biortech.2016.07.061 denitrification efficiency in the external aerobic/anoxic reactor declined due to insufficient biodegradable COD (Semblante et al, 2016). In this study, the soluble COD/nitrate-nitrogen ratio at different external reactor SRTs were similar to each other (Table 3) and were consistently close to the theoretical value of 3.7 (Chiu & Chung, 2003), which suggests that soluble COD would have been available for denitrification throughout the operation period.…”
Section: Mechanism Of Sludge Reductionmentioning
confidence: 99%
“…A previous study have demonstrated that sludge reduction in this particular OSA configuration ( Figure 1) is due to the destruction of volatile solids in the external anoxic reactor, followed by the conversion of destroyed solids into inert products via nitrification/denitrification in the external aerobic/anoxic reactor (Semblante et al, 2016). In this study, the nutrient concentration ( Figure 5) and ORP ( Figure 6) of the external reactors were monitored to provide insight into the effect of SRT on the aforementioned biochemical reactions.…”
Section: Mechanism Of Sludge Reductionmentioning
confidence: 99%